Sodium ferric sulfate positive electrode material and preparation method thereof
Through solid-phase ball milling treatment and two-stage sintering technology, combined with the coordinated cooperation of inorganic sodium salt and organic sodium salt, a large-scale production of suitable sodium ferrosulfate cathode material with excellent air stability and circulation stability was prepared, solving the problem of insufficient material stability in the prior art.
Patent Information
- Application Number
- CN202411706031.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-14
AI Technical Summary
The air stability and circulation stability of sodium ferrous sulfate cathode material are poor, which limits its industrialization process.
Sodium iron sulfate positive electrode material is prepared through solid-phase ball milling treatment and two-stage sintering technology. Combined with the coordinated cooperation of inorganic sodium salt and organic sodium salt, a more stable crystal structure and three-dimensional channel are formed, improving the air stability and circulation stability of the material.
It achieves excellent air stability and circulation stability of sodium ferrosulfate cathode material, reduces production costs, and is suitable for large-scale production applications.
Smart Images

Figure CN119612598A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ferric sulfate positive electrode material preparation, and in particular to a sodium ferric sulfate positive electrode material and a preparation method thereof. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries have obvious advantages in high and low temperature performance, rate performance, etc., and their resources are abundant and the expected cost is low. Therefore, sodium-ion batteries have become the optimal solution for energy storage and light electric vehicles. At present, among the three major positive electrode materials for sodium-ion batteries, polyanion sodium positive electrodes stand out with their advantages of long cycle life, stable structure, and high operating voltage, becoming the most suitable positive electrode material for sodium-ion batteries for long-term energy storage.
[0003] At present, there are two main types of polyanion materials, namely composite phosphates and sulfates. Composite phosphate materials have good air stability but low energy density, and lack of development space. Sulfate polyanion materials have a higher working voltage due to the stronger inductive effect of sulfate ions, and sodium iron sulfate materials are expected to be the lowest-priced polyanion sodium cathode materials, which is in line with the low-cost strategy of sodium ion batteries. In addition, due to its high charge and discharge platform, which is basically consistent with the charge and discharge platform of high-nickel ternary materials, this material has a unique advantage in mixing with high-nickel ternary materials. Therefore, sodium iron sulfate material has become one of the most promising sodium ion battery cathode materials at present, but sodium iron sulfate series materials often face the problems of low capacity, high resistivity, poor processing performance, and poor air stability, which in turn limits its industrialization process.
[0004] Atomic doping and surface coating of positive electrode materials are currently commonly used modification methods for positive electrode materials, which are used to improve the reversible specific capacity of the battery and reduce the internal resistance between materials. Existing literature mainly solves the above problems by carbon coating sodium ferric sulfate materials. Among them, a preparation method of a sodium ferric sulfate positive electrode material is disclosed in a Chinese patent application with a patent application publication number of CN118231633A. The sodium ferric sulfate positive electrode material disclosed in the preparation method includes a sodium ferric sulfate core and a first coating layer and a second coating layer coated on the surface of the sodium ferric sulfate core. By setting the coating layer, the dissolution of iron ions can be reduced, while avoiding blocking the sodium ion transmission channel, so that the sodium ferric sulfate positive electrode material has the advantages of high cycle performance and high specific capacity. However, the high cycle performance of the sodium ferric sulfate positive electrode material still needs to be improved, and research on the air stability of sodium ferric sulfate is rarely involved. Summary of the invention
[0005] The main purpose of the present invention is to provide a sodium ferric sulfate positive electrode material and a preparation method thereof, so as to solve the problem of poor air stability and cycle stability of sodium ferric sulfate in the prior art.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a sodium ferric sulfate positive electrode material is provided, and the preparation method comprises: step S1, subjecting raw materials including a sodium source, an iron source, an antioxidant and a conductive agent to solid-phase ball milling to obtain a ball-milled material; step S2, in an inert atmosphere, subjecting the ball-milled material to a first sintering and a second sintering in sequence to obtain a sodium ferric sulfate positive electrode material; wherein the sodium source comprises an inorganic sodium salt and an organic sodium salt, and the temperature of the second sintering is greater than the temperature of the first sintering.
[0007] Furthermore, the above-mentioned inorganic sodium salt is selected from any one or more of sodium sulfate, sodium phosphate and sodium hydrogen phosphate; and / or the organic sodium salt is selected from any one or more of sodium acetate, sodium oxalate, sodium stearate, sodium oleate and sodium citrate; and / or, the molar ratio of the inorganic sodium salt to the organic sodium salt is (0.8-1.1):(0.1-0.5).
[0008] Furthermore, in the above step S1, the ratio of the total molar number of sodium element in the sodium source to the total molar number of iron element in the iron source is (1.8-2.9): (1.7-2.1).
[0009] Furthermore, in the above step S1, the antioxidant is selected from any one or more of ascorbic acid, citric acid, caffeic acid and gallic acid.
[0010] Furthermore, in the above step S1, the temperature of the solid phase ball milling treatment is 90°C to 450°C, and / or the time of the solid phase ball milling treatment is 15h to 20h, and / or the ball-to-material ratio during the solid phase ball milling treatment is (2 to 10):1.
[0011] Furthermore, in the above step S1, the median particle size D50 of the ball-milled material is 1 μm to 10 μm.
[0012] Furthermore, in the above step S1, the conductive agent is selected from any one or more of carbon nanotubes, SP conductive agent, and acetylene black conductive agent.
[0013] Furthermore, in the above step S2, the temperature of the first sintering is 90°C to 200°C, preferably 100°C to 150°C, the heating rate of the first sintering is preferably 1°C / min to 3°C / min, and the time of the first sintering is preferably 5h to 15h.
[0014] Furthermore, in the above step S2, the temperature of the second sintering is 201°C to 450°C, preferably 300°C to 400°C, the heating rate of the second sintering is preferably 3°C / min to 7°C / min, and the time of the second sintering is preferably 10h to 24h.
[0015] According to another aspect of the present invention, a sodium iron sulfate positive electrode material is provided. The sodium iron sulfate positive electrode material is prepared by the aforementioned preparation method.
[0016] Applying the technical scheme of the present invention, the preparation method of the present invention, on the one hand, introduces inorganic sodium salt and organic sodium salt at the same time, so that inorganic anions and organic anions exist in the preparation system of sodium ferric sulfate positive electrode material at the same time, and then utilizes the difference of electronic effect and spatial effect of inorganic anions and organic anions and the synergistic effect of the two, so that the sodium ferric sulfate positive electrode material has stronger ionic bonds and covalent bonds, thereby improving the stability of the crystal structure of the sodium ferric sulfate positive electrode material. On the other hand, through solid phase ball milling treatment and two-stage sintering technology, the three-dimensional channel in the crystal structure of the sodium ferric sulfate positive electrode material is more conducive to the passage of sodium ions. Through the synergistic effect of the above two aspects, the prepared sodium ferric sulfate positive electrode material has both excellent air stability and cycle stability. In addition, the above preparation method is simple to operate, low in production cost, and suitable for large-scale production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 A cycle capacity retention rate curve of a sodium ion battery corresponding to the sodium iron sulfate positive electrode material obtained according to Examples 1 to 4 of the present invention and Comparative Example 1 is shown. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] As analyzed in the background technology, sodium ferric sulfate in the prior art has the problem of poor air stability and cycle stability. To solve this problem, the present invention provides a sodium ferric sulfate positive electrode material with high air stability and a preparation method thereof.
[0021] In a typical embodiment of the present application, a method for preparing a sodium ferric sulfate positive electrode material is provided, and the preparation method comprises: step S1, subjecting raw materials including a sodium source, an iron source, an antioxidant and a conductive agent to solid-phase ball milling to obtain a ball-milled material; step S2, in an inert atmosphere, subjecting the ball-milled material to a first sintering and a second sintering in sequence to obtain a sodium ferric sulfate positive electrode material; wherein the sodium source comprises an inorganic sodium salt and an organic sodium salt, and the temperature of the second sintering is greater than the temperature of the first sintering.
[0022] The preparation method of the present invention, on the one hand, introduces inorganic sodium salt and organic sodium salt at the same time, so that inorganic anions and organic anions exist in the preparation system of sodium ferric sulfate positive electrode material at the same time, and then utilizes the difference of electronic effect and space effect of inorganic anions and organic anions and the synergistic effect of the two, so that the sodium ferric sulfate positive electrode material has stronger ionic bonds and covalent bonds, thereby improving the stability of the crystal structure of the sodium ferric sulfate positive electrode material. On the other hand, through solid phase ball milling treatment and two-stage sintering technology, the three-dimensional channel in the crystal structure of the sodium ferric sulfate positive electrode material is more conducive to the passage of sodium ions. Through the synergistic effect of the above two aspects, the prepared sodium ferric sulfate positive electrode material has excellent air stability and cycle stability. In addition, the above preparation method is simple to operate, low in production cost, and suitable for large-scale production applications.
[0023] Furthermore, it is preferred that the inert atmosphere be nitrogen or argon.
[0024] In one embodiment of the present application, the inorganic sodium salt is selected from any one or more of sodium sulfate, sodium phosphate and sodium hydrogen phosphate; and / or the organic sodium salt is selected from any one or more of sodium acetate, sodium oxalate, sodium stearate, sodium oleate and sodium citrate; and / or the molar ratio of the inorganic sodium salt to the organic sodium salt is (0.8-1.1):(0.1-0.5).
[0025] The preferred types of the above inorganic sodium salt and organic sodium salt and the mass ratio of the two are within the above range, which is more conducive to improving the synergistic coordination of the corresponding anions of the two, thereby providing favorable spatial effects and electronic effects for the formation of strong ionic bonds, strong covalent bonds and three-dimensional channels in the crystal structure of the sodium ferric sulfate positive electrode material. Further, the control of the mass ratio of the preferred inorganic sodium salt and the organic sodium salt is conducive to further achieving the optimal result through the synergistic coordination of multiple anions.
[0026] In one embodiment of the present application, in the above step S1, the ratio of the total molar number of sodium element in the sodium source to the total molar number of iron element in the iron source is (1.8-2.9): (1.7-2.1).
[0027] By controlling the ratio of the total molar number of sodium element in the sodium source to the total molar number of iron element in the iron source within the above range, it is beneficial to improve the specific capacity, rate performance and cycle stability of the sodium iron sulfate positive electrode material.
[0028] In one embodiment of the present application, in the above step S1, the antioxidant is selected from any one or more of ascorbic acid, citric acid, caffeic acid and gallic acid.
[0029] In the preparation method of the present application, by adding an antioxidant, Fe 2+ of oxidation.
[0030] In one embodiment of the present application, in the above step S1, the temperature of the solid phase ball milling treatment is 90°C to 450°C, and / or the time of the solid phase ball milling treatment is 15h to 20h, and / or the ball-to-material ratio during the solid phase ball milling treatment is (2 to 10):1.
[0031] By controlling the temperature and time of the solid phase ball milling treatment within the above range, it is beneficial to mix the raw materials including the sodium source, the iron source, the antioxidant, and the conductive agent more evenly, thereby improving the effect and efficiency of the solid phase ball milling of the raw materials. Preferably, the ball-to-material ratio during the solid phase ball milling treatment is within the above range, which is beneficial to further improve the mixing uniformity and grain refinement of the raw materials.
[0032] In one embodiment of the present application, in the above step S1, the median particle size D50 of the ball-milled material is 1 μm to 10 μm.
[0033] By controlling the median particle size D50 of the ball-milled material within the above range, it is beneficial to improve the compaction density of the battery pole piece, thereby increasing the discharge capacity of the battery, reducing the internal resistance, and extending the cycle stability of the battery.
[0034] In one embodiment of the present application, in the above step S1, the conductive agent is selected from any one or more of carbon nanotubes, SP conductive agent, and acetylene black conductive agent.
[0035] In the preparation method of the present application, by adding a conductive agent, the conductivity of the sodium iron sulfate positive electrode material can be improved, which is beneficial to improving the overall electrical performance of the battery.
[0036] In one embodiment of the present application, in the above step S2, the temperature of the first sintering is 90°C to 200°C, preferably 100°C to 150°C, the heating rate of the first sintering is preferably 1°C / min to 3°C / min, and the time of the first sintering is preferably 5h to 15h.
[0037] The above preferred first sintering conditions are helpful to remove moisture and impurities in the reaction system.
[0038] In one embodiment of the present application, in the above step S2, the temperature of the second sintering is 201°C to 450°C, preferably 300°C to 400°C, the heating rate of the second sintering is preferably 3°C / min to 7°C / min, and the time of the second sintering is preferably 10h to 24h.
[0039] The preferred second sintering condition above is helpful to improve the formation of the crystal structure of the sodium iron sulfate positive electrode material, thereby obtaining a sodium iron sulfate positive electrode material with better air stability and cycle stability.
[0040] In another typical embodiment of the present application, a sodium iron sulfate positive electrode material is provided, and the sodium iron sulfate positive electrode material is prepared by the aforementioned preparation method.
[0041] Since the sodium iron sulfate positive electrode material is prepared by the aforementioned preparation method, the sodium iron sulfate positive electrode material has high air stability and cycle stability.
[0042] Furthermore, the D10 particle size of the sodium ferric sulfate positive electrode material is preferably 2 μm to 3 μm, the D50 particle size of the sodium ferric sulfate positive electrode material is preferably 6 μm to 8 μm; and the D90 particle size of the sodium ferric sulfate positive electrode material is preferably 11 μm to 12 μm.
[0043] In a preferred embodiment of the present application, a method for preparing a sodium ferric sulfate positive electrode sheet is also provided, comprising stirring and mixing the sodium ferric sulfate positive electrode material prepared by the above method with a conductive agent, PVDF and NMP respectively to obtain a positive electrode slurry, wherein the mass ratio of the sodium ferric sulfate positive electrode material: the conductive agent: the binder is preferably 80-90:5-10:5-10; applying the above positive electrode slurry on the positive electrode collector, vacuum drying it and then punching it into small discs with a diameter of 14 mm.
[0044] Since the above-mentioned sodium ferric sulfate positive electrode plate is prepared from the sodium ferric sulfate positive electrode material of the present application, the sodium ferric sulfate positive electrode plate has higher air stability and cycle stability.
[0045] The beneficial technical effects of the present application will be described below in combination with specific embodiments and comparative examples.
[0046] Example 1
[0047] FeSO4(AR), Na2SO4(AR), Na3PO4(AR), sodium stearate, ascorbic acid and carbon nanotubes were used as raw materials for solid phase ball milling; wherein the molar ratio of FeSO4:Na2SO4:Na3PO4 and sodium stearate was 0.18:0.09:0.02:0.05; ascorbic acid accounted for 2% of the total mass of the raw materials, and carbon nanotubes accounted for 1% of the total mass of the raw materials; the mixture was placed in a ball mill to ensure that the ball-to-material ratio was 10:1, and high-speed ball milling was performed for 15 hours to obtain a ball-milled material, and the median particle size D50 of the ball-milled material was 7μm.
[0048] 50 g of the ball-milled material was placed in a drying oven at 90°C for vacuum drying for 10 hours, and then placed in a tubular furnace. In an argon atmosphere, the temperature was raised to 150°C at a heating rate of 2°C / min for the first sintering, and the temperature was kept for 10 hours. After the first sintering, the temperature was raised to 350°C at a heating rate of 5°C / min for the second sintering, and the temperature was kept for 15 hours. After the second sintering, the sodium iron sulfate positive electrode material was obtained.
[0049] Example 2
[0050] FeSO4(AR), Na2SO4(AR), Na3PO4(AR), sodium stearate, ascorbic acid and carbon nanotubes are used as raw materials for ball milling and mixing; wherein the molar ratio of FeSO4:Na2SO4:Na3PO4:sodium stearate is 0.21:0.06:0.03:0.03; ascorbic acid accounts for 2% of the total mass of the raw materials, and carbon nanotubes account for 1% of the total mass of the raw materials; the mixture is placed in a ball mill to ensure that the ball-to-material ratio is 10:1, and high-speed ball milling is performed for 15 hours to obtain a ball-milled material, and the median particle size D50 of the ball-milled material is 7μm.
[0051] 50 g of the ball-milled material was placed in a drying oven at 90°C for vacuum drying for 10 hours, and then placed in a tubular furnace. In an argon atmosphere, the temperature was raised to 150°C at a heating rate of 2°C / min for the first sintering, and the temperature was kept for 10 hours. After the first sintering, the temperature was raised to 350°C at a heating rate of 5°C / min for the second sintering, and the temperature was kept for 15 hours. After the second sintering, the sodium iron sulfate positive electrode material was obtained.
[0052] Example 3
[0053] The difference from Example 1 is that FeSO4(AR), Na2SO4(AR), Na3PO4(AR), sodium citrate, ascorbic acid and carbon nanotubes are used as raw materials for ball milling and mixing; the molar ratio of FeSO4:Na2SO4:Na3PO4:sodium citrate is 0.21:0.06:0.03:0.01; and finally sodium iron sulfate positive electrode material is obtained.
[0054] Example 4
[0055] The difference from Example 1 is that FeSO4(AR), Na2SO4(AR), Na3PO4(AR), sodium oxalate, sodium stearate, ascorbic acid and carbon nanotubes are used as raw materials for ball milling and mixing; the molar ratio of FeSO4:Na2SO4:Na3PO4:sodium oxalate:sodium stearate is 0.21:0.06:0.03:0.005:0.01; and finally sodium iron sulfate positive electrode material is obtained.
[0056] Example 5
[0057] The difference from Example 1 is that FeSO4(AR), Na2SO4(AR), Na3PO4(AR), sodium oxalate, sodium stearate, ascorbic acid and carbon nanotubes are used as raw materials for ball milling and mixing; the molar ratio of FeSO4:Na2SO4:Na3PO4:sodium oxalate:sodium stearate is 0.21:0.06:0.03:0.004:0.012; and finally sodium ferric sulfate positive electrode material is obtained.
[0058] Example 6
[0059] The difference from Example 1 is that FeSO4(AR), Na2SO4(AR), Na3PO4(AR), sodium oxalate, sodium stearate, ascorbic acid and carbon nanotubes are used as raw materials for ball milling and mixing; the molar ratio of FeSO4:Na2SO4:Na3PO4:sodium oxalate:sodium stearate is 0.21:0.05:0.02:0.005:0.01; and finally sodium ferric sulfate positive electrode material is obtained.
[0060] Example 7
[0061] The difference from Example 4 is that the molar ratio of FeSO4:Na2SO4:Na3PO4:sodium oxalate:sodium stearate is 0.20:0.06:0.03:0.005:0.01; and finally a sodium iron sulfate positive electrode material is obtained.
[0062] Example 8
[0063] The difference from Example 4 is that the molar ratio of FeSO4:Na2SO4:Na3PO4:sodium oxalate:sodium stearate is 0.22:0.05:0.03:0.01:0.01; and finally a sodium iron sulfate positive electrode material is obtained.
[0064] Example 9
[0065] The difference from Example 1 is that the ball-to-material ratio is 2:1, and high-speed ball milling is performed for 20 hours to finally obtain sodium iron sulfate positive electrode material.
[0066] Example 10
[0067] The difference from Example 1 is that the ball-to-material ratio is 15:1, and high-speed ball milling is performed for 10 hours to finally obtain sodium iron sulfate positive electrode material.
[0068] Embodiment 11
[0069] The difference from Example 1 is that in an argon atmosphere, the temperature is raised to 90° C. at a heating rate of 2° C. / min for the first sintering, and the temperature is kept for 15 hours to finally obtain a sodium iron sulfate positive electrode material.
[0070] Example 12
[0071] The difference from Example 1 is that after the first sintering is completed, the temperature is raised to 450° C. at a heating rate of 5° C. / min for the second sintering, and the temperature is kept for 10 hours to finally obtain the sodium iron sulfate positive electrode material.
[0072] Comparative Example 1
[0073] The difference from Example 2 is that FeSO4(AR), Na2SO4(AR), ascorbic acid and carbon nanotubes are used as raw materials for ball milling and mixing; the molar ratio of FeSO4:Na2SO4 is 0.18:0.12; and finally sodium iron sulfate positive electrode material is obtained.
[0074] Comparative Example 2
[0075] The difference from Example 2 is that FeSO4 (AR), sodium oxalate, ascorbic acid and carbon nanotubes are used as raw materials for ball milling and mixing; the molar ratio of FeSO4: sodium oxalate is 0.18:0.12; and finally sodium iron sulfate positive electrode material is obtained.
[0076] Comparative Example 3
[0077] The difference from Example 1 is that only one sintering is performed and the sintering is only performed at 350° C. for 15 h, and finally a sodium iron sulfate positive electrode material is obtained.
[0078] Performance Testing:
[0079] Particle size of sodium ferric sulfate positive electrode material: Malvern laser particle size analyzer was used to count the D10 particle size, D50 particle size and D90 particle size of the sodium ferric sulfate positive electrode material, and the test results are listed in Table 1.
[0080] Take the sodium iron sulfate positive electrode material prepared in the above embodiment and comparative example respectively, and then stir and mix it with SP conductive agent, PVDF and NMP to obtain positive electrode slurry, wherein the mass ratio of sodium iron sulfate positive electrode material: conductive agent: binder is 90:5:5. The above positive electrode slurry is coated on the positive electrode collector, and after vacuum drying, it is punched into small discs with a diameter of 14 mm, namely the positive electrode sheet. Then, the above positive electrode sheet, sodium metal sheet, diaphragm, and electrolyte are assembled into button batteries for charge and discharge experiments to test the electrochemical properties of the sodium iron sulfate positive electrode material. The positive electrode sheet loading is 10-30 mg / cm 2 , the baking temperature is 90℃, and the time is 15-20h. The voltage range selected in the electrochemical test is 2.0-4.3V, the charge and discharge rate is 0.5C / 0.5C, and the 0.5C gram capacity and the discharge efficiency at 0.5C are calculated and listed in Table 1. The initial capacity test is measured by assembling the battery immediately after the material is sintered. The process humidity is 15%-25% and the temperature is 25℃±5℃. The capacity of the sodium iron sulfate positive electrode material after exposure to a humidity environment of 50±10% for 1h, 3h, 10h, and 24h is tested and listed in Table 2.
[0081] Table 1
[0082]
[0083]
[0084] Table 2
[0085]
[0086] The cycle capacity retention rate curve of the sodium ion battery corresponding to the sodium iron sulfate positive electrode material obtained in Examples 1 to 4 and Comparative Example 1 is as follows: Figure 1 shown.
[0087] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0088] The preparation method of the present invention, on the one hand, introduces inorganic sodium salt and organic sodium salt at the same time, so that inorganic anions and organic anions exist in the preparation system of sodium ferric sulfate positive electrode material at the same time, and then utilizes the difference of electronic effect and space effect of inorganic anions and organic anions and the synergistic effect of the two, so that the sodium ferric sulfate positive electrode material has stronger ionic bonds and covalent bonds, thereby improving the stability of the crystal structure of the sodium ferric sulfate positive electrode material. On the other hand, through solid phase ball milling treatment and two-stage sintering technology, the three-dimensional channel in the crystal structure of the sodium ferric sulfate positive electrode material is more conducive to the passage of sodium ions. Through the synergistic effect of the above two aspects, the prepared sodium ferric sulfate positive electrode material has excellent air stability and cycle stability. In addition, the above preparation method is simple to operate, low in production cost, and suitable for large-scale production applications.
[0089] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a sodium iron sulfate positive electrode material, characterized in that: The preparation method comprises: Step S1, subjecting raw materials including a sodium source, an iron source, an antioxidant and a conductive agent to solid phase ball milling to obtain a ball milled material; Step S2, in an inert atmosphere, sequentially performing a first sintering and a second sintering on the ball-milled material to obtain a sodium iron sulfate positive electrode material; Wherein, the sodium source includes an inorganic sodium salt and an organic sodium salt, and the temperature of the second sintering is greater than the temperature of the first sintering.
2. The preparation method according to claim 1, characterized in that: The inorganic sodium salt is selected from any one or more of sodium sulfate, sodium phosphate and sodium hydrogen phosphate; and / or the organic sodium salt is selected from any one or more of sodium acetate, sodium oxalate, sodium stearate, sodium oleate and sodium citrate; and / or the molar ratio of the inorganic sodium salt to the organic sodium salt is (0.8-1.1):(0.1-0.5).
3. The preparation method according to claim 1 or 2, characterized in that: In the step S1, the ratio of the total molar number of sodium element in the sodium source to the total molar number of iron element in the iron source is (1.8-2.9): (1.7-2.1).
4. The preparation method according to any one of claims 1 to 3, characterized in that In the step S1, the antioxidant is selected from any one or more of ascorbic acid, citric acid, caffeic acid and gallic acid.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S1, the temperature of the solid phase ball milling treatment is 90°C to 450°C, and / or the time of the solid phase ball milling treatment is 15h to 20h, and / or the ball-to-material ratio during the solid phase ball milling treatment is (2 to 10):
1.
6. The preparation method according to any one of claims 1 to 5, characterized in that In the step S1, the median particle size D50 of the ball-milled material is 1 μm to 10 μm.
7. The preparation method according to any one of claims 1 to 6, characterized in that In the step S1, the conductive agent is selected from any one or more of carbon nanotubes, SP conductive agent, and acetylene black conductive agent.
8. The preparation method according to any one of claims 1 to 7, characterized in that In the step S2, the temperature of the first sintering is 90°C to 200°C, preferably 100°C to 150°C, the heating rate of the first sintering is preferably 1°C / min to 3°C / min, and the time of the first sintering is preferably 5h to 15h.
9. The preparation method according to any one of claims 1 to 8, characterized in that: In the step S2, the temperature of the second sintering is 201°C to 450°C, preferably 300°C to 400°C, the heating rate of the second sintering is preferably 3°C / min to 7°C / min, and the time of the second sintering is preferably 10h to 24h.
10. A sodium iron sulfate positive electrode material, characterized in that: The sodium iron sulfate positive electrode material is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Sodium ferric sulfate positive electrode material, preparation method thereof, positive plate and battery
CN118231633A